PMO-012 Improving the patient journey in hepatology: the efficacy of pre-appointment investigations. (28th May 2012) - Lever, C; House, J; Ramaharack, S; Sheron, N; Wright, M
Abstract : Introduction: Most patients attending hepatology clinic for the first time require a basic liver screen before a definitive diagnosis or plan of action can be made. We sought to establish if doing these tests prior to the visit could speed up the patient journey. Methods: New referrals appraised by a consultant hepatologist and considered for routine outpatient appointments were entered in to the pre-appointment investigation study. 58 patients during July and August 2010 were sent blood forms and booked for ultrasound to be completed before coming to the first consultation. Of the 58 patients 55 were eligible for analysis. Results: 17 (30%) patients had all blood results available at clinic, 30 (54%) patients had imaging reports available and 10 (18%) had both. At first consultation Nine patients were discharged back to the GP One booked for MRCP, discharged from clinic One had no follow-up booked Three discharged to the nurse led clinic One booked into the virtual clinic One went for TACE 16 (29%) of patients did not require a follow-up appointment in a consultant led hepatology clinic with 11 of these patients requiring no follow-up at all. 49 out of the 55 (89%) patients had a definite diagnosis made at the first clinic appointment, verified subsequently by imaging and blood results. Compared to the same time frame for the year before a fivefold increase (from 4.3% to 20%) in discharges to GP was achievable. Conclusion: This involves a commitment to arrange blood tests and imaging in advance, the costs are no different as these are routine investigations. With blood results available at the first consultation there was a significant increase in discharges. Simply changing the order of interventions results in a reduction in follow-up allocations, with an associated increase in the speed of patient progression across all clinics. Moving 89% of the patients seen in hepatology clinic on to the correct pathway at the first consultation, saves time and money. Competing interests: None declared.